Faktor-Faktor yang Mempengaruhi Motivasi Filantropi Mahasiswa melalui Pembayaran Zakat, Infaq dan Shadaqah - Fitriati Akmila; Rosmana Sandy; Fany Indriyani (Jurnal Ekonomi Islam, 2022)
The purpose of this research is to analyse the impact zakat knowledge, infaq and sadaqah, religiosity, self-awareness, social environment and convenience on student motivation in paying zakat, infaq and sadaqah. The research sample used purposive sampling method. The population of this study were the 2017-2020 academic year students of the Faculty of Business & Economics, Universitas Islam Indonesia. 251 respondents were taken as samples. This study used primary data by sending an online questionnaire to FBE UII students. Multiple linear regression method is used for analysis. The results of this study indicated that Zakat knowledge, infaq and shadaqah, religiosity, self-awareness, social environment and convenience have a positive and significant influence on student motivation in paying zakat, infaq & shadaqah. In conclusion accounting students of the Faculty of Business and Economics, Universitas Islam Indonesia have high motivation in paying Zakat, Infaq & Sadaqah.